2000
DOI: 10.1103/physrevb.62.10867
|View full text |Cite
|
Sign up to set email alerts
|

Hole conductivity and compensation in epitaxial GaN:Mg layers

Abstract: The concentration p and the mobility mu of holes in metal-organic chemical vapor deposition (MOCVD) GaN:Mg layers were studied by room temperature Hall-effect measurements as a function of the Mg concentration N(A) in the range 3 x 10(exp 18) cm(exp-3) <= N(A) <= 1 x 10(exp 20) cm(exp -3). The hole density first increases with increasing N(A), reaches a maximum value p(max)~6*10(exp 17) cm(exp -3) at N(A)~2*10(exp 19) cm(exp - 3), decreases for larger N(A) values, and drops to very small values at N(A) 1 x 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
193
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(208 citation statements)
references
References 19 publications
(21 reference statements)
12
193
2
1
Order By: Relevance
“…Further increase of the Mg concentration, up to 1x10 20 cm -3 leads to a decrease of the free hole concentration. This is commonly interpreted as auto-compensation due to increased formation of N vacancies or vacancy complexes with Mg [1]. Another characteristic feature is the occurrence of the so-called "blue band" in the photoluminescence spectra of highly Mgdoped GaN grown by MOVPE [2].…”
Section: Introductionmentioning
confidence: 99%
“…Further increase of the Mg concentration, up to 1x10 20 cm -3 leads to a decrease of the free hole concentration. This is commonly interpreted as auto-compensation due to increased formation of N vacancies or vacancy complexes with Mg [1]. Another characteristic feature is the occurrence of the so-called "blue band" in the photoluminescence spectra of highly Mgdoped GaN grown by MOVPE [2].…”
Section: Introductionmentioning
confidence: 99%
“…To compare the electrical properties of p-type ZnO and GaN, we note that, for Mg-doped, p-type GaN, typical values of p and p are about 5 cm 2 /V s and 1ϫ10 17 cm Ϫ3 , respectively, 29,31 close to our measured values for N-doped, p-type ZnO. Moreover, any reported values of p and p much higher than these in GaN should be viewed with some caution, as will be discussed later.…”
mentioning
confidence: 99%
“…In the moderate doping regime, 3 x 10 18 cm -3 ≤ N A ≤ 2 x 10 19 cm -3 , H passivation is very effective and impurity compensation as well as self-compensation mechanisms are negligible [4]. The effect of a doping-driven compensation becomes significant when the Mg concentration exceeds a value of N A ≥ 2 x 10 19 cm -3 .…”
Section: Resultsmentioning
confidence: 91%
“…The origin of this band is still not completely understood and recent experimental results indicate that it might consist of more than one emission band [5,22]. Most researchers agree that the blue band is caused by a transition between a deep localized donor and an acceptor state (likely a Mg-related acceptor) [4,5,23]. Both theoretical [4,24] and experimental [4,5] studies concluded that the incorporation of high Mg concentrations is accompanied by a formation of additional deep donors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation